Pelatihan dan Pendampingan untuk Meningkatkan Potensi Usaha Mikro, Kecil, dan Mengenah (UMKM) di Kelurahan Sawitan - Nurjanah Nurjanah; Nasihin Nasihin; Tiyas Indriyani; Arum Isnadiyati; Abit Sabita; Prita Noviana; Annisa Nurul Jannah; Sri Ranti Wahyuningsih; Syafa Maulidya Nur; Happy Wuldatus Safithri; Atika Shofiya Loerensa; Parel Asropi; Avrillaila Akbar Harahap (Warta LPM, 2024)
Sawitan Village is an area that is included in the industrial village category because the majority of its residents work as business managers. Situated in an area that passes through the Borobudur tourism route, Sawitan Village has a strategic location and encourages its residents to work as business people. Based on data collection, there are 113 MSMEs in Sawitan Village with the majority of business types being the culinary sector, reaching 48%. Other types of businesses include non-food production, grocery stores, fashion, livestock, agribusiness and services. The large number of MSMEs can be a regional potential in improving the level of community welfare. However, there are still many MSME players who do not understand the aspects that can support their business. This is evidenced by the low level of understanding of digitalization, namely 48%, completeness of business legality only reaching 5%, and understanding of financial literacy only reaching 18%. The aim of community service carried out by the Alma Ata University KKN-T team is to increase the understanding and motivation of MSME actors in developing MSME potential through the digitalization of MSMEs, complete business legality, and good financial management. The method used in implementing this activity is the Participatory Action Research (PAR) approach. The results of community service show that the enthusiasm of MSME players has increased by 75% to implement digital marketing and complete business licensing.